Pengaruh Insentif Dan Disiplin Terhadap Motivasi Serta Dampaknya Pada Kinerja Pegawai Satuan Polisi Pamong Praja Kabupaten Batang Hari - M Zahari MS; Evi Adriani; Muhammad Harli Hamdani (Universitas Batanghari, 2019)
This research was conducted in the police unit of Pamong Praja Batang Hari District as part of regional devices in the enforcement and public order implementation and community tranquility. The purpose of this research is to see how the incentive impact and the discipline of motivation and impact on performance of police unit Pamong Praja Batang Hari District. This research is a research using a method of descriptive and verificative research, which is a method of researching a human group, an object, the situation and condition of a system of thought with a purpose to make a description, a systematic picture according to the facts being investigated. The verificative research aims to examine the hypothesis of the influence between variables of this study. The samples in this study used the census method, which is all employees in the police unit of Batang Hari Distrct, while the data used in this research is the primary data obtained from the results of the statement in questionnaire provided and has been filled by each employee in the police unit Pamong Praja Batang Hari District, the data analysis technique that data used is path analysis, with the help of software program SPSS version 22. The results of this study showed that the free variables of incentive and discipline positively and significantly affect the employee's motivation and have a positive and significant impact on the employee performance of the Pamong Praja Police unit at Batang Hari District, this proves that with the increase of incentives and discipline in the police unit Pamong Praja Batang Hari District, it will also increase the motivation that will impact the improvement of employee performance in the police unit Pamong Praja Batang Hari District.